The given functions are
![\begin{gathered} f(x)=2x^3-14x^2+bx-3 \\ g(x)=x^3+cx^2-8x+30 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7ig45yank6vxyvd79pqkdwgii117sffwvw.png)
Since f(x) has a zero x = 2, then
Substitute x by 2 and equate the answer by 0 to find b
![\begin{gathered} f(2)=0 \\ 2(2)^3-14(2)^2+b(2)-3=0 \\ 2(8)-14(4)+2b-3=0 \\ 16-56+2b-3=0 \\ (16-56-3)+2b=0 \\ -43+2b=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6yephrmepums90k3bhdvgprtnisy9mbwgx.png)
Add 43 to both sides
![\begin{gathered} -43+43+2b=0+43 \\ 2b=43 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/puro0dibgbrpkl1octc11fc9mbi1aexzbg.png)
Divide both sides by 2
![\begin{gathered} (2b)/(2)=(43)/(2) \\ b=(43)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6b7by526vvoc981fsqb2b35ikqc1cty0lz.png)
Then, f(x) is
![f(x)=2x^3-14x^2+(43)/(2)x-3](https://img.qammunity.org/2023/formulas/mathematics/college/9u8dy5v735lupxeo14dw5l7cualtwkseqt.png)
We will do the same with g(x)
Since g(x) has a root x = 3 - i, then there is another root x = 3 + i
Then substitute x by 3 - i and equate the answer by 0
![\begin{gathered} g(x-i)=0 \\ (3-i)^3+c(3-i)^2-8(3-i)+30=0 \\ (3-i)(3-i)^2+c(9-6i+i^2)-24+8i+30=0 \\ (3-i)(9-6i+i^2)+c(8-6i)-24+8i+30=0 \\ 27-18i+3i^2-9i+6i^2-i^3+c(8-6i)-24+8i+30=0 \\ 27-18i-3-9i-6+i+c(8-6i)-24+8i+30=0 \\ (27-3-6-24+30)+(-18i-9i+i+8i)+c(8-6i)=0 \\ 24+(-18i)+c(8-6i)=0 \\ 24-18i+c(8-6i)=0 \\ 8c-6ic=-24+18i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/50s2fwqns466m3nfwuhqgeukr2y8eu3gc9.png)
By comparing the 2 sides, then
![\begin{gathered} 8c=-24 \\ (8c)/(8)=(-24)/(8) \\ c=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5vlccdp5phtl682736yf9zz0gm2y1dvypm.png)
Then g(x) is
![g(x)=x^3-3x^2-8x+30](https://img.qammunity.org/2023/formulas/mathematics/college/wpgmcu6vagkuhfr7ktnil19t6ujdla2e76.png)
Now, multiply f and g, then substitute x by -1
![(f\ast g)(-1)=\lbrack2(-1)^3-14(-1)^2+(43)/(2)(-1)-3\rbrack\ast\lbrack(-1)^3-3(-1)^2-8(-1)+30\rbrack](https://img.qammunity.org/2023/formulas/mathematics/college/9kuutx58b7mag7l2f23hke15yqxavdout8.png)
Simplify each bracket
![\begin{gathered} (f\ast g)(-1)=\lbrack-2-14-(43)/(2)-3\rbrack\lbrack-1-3+8+30\rbrack \\ (f\ast g)(-1)=\lbrack-(77)/(2)\rbrack\ast\lbrack34\rbrack \\ (f\ast g)(-1)=-1309 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/helqdw3cfn4lqdq61jejxsryx8ut2uwboi.png)
The answer is -1309